SANTRI AND ABANGAN AFTER A HALF CENTURY OF CLIFFORD GEERTZ - Amanah Nurish (Islam Futura, 2021)
This research paper analyzes the religious phenomenon of culture in Modjokuto or Pare, where Geertz carried out his thesis on the "Religion of Java." Although there are many pesantrens in Modjokuto, there is still a religious tradition associated with Kejawen as a local belief, particularly among rural Muslim farmers. Javanese mysticism, however, plays an important part in muslim abangan. Some rural villages in Modjokuto, both NU and Muhammadiyah, are not very distinct in religious tradition. They have performed slametan, tahlilan, and ziarah as religious rituals. Kejawen's teachings are more observed by traditionalist Moslems in Modjokuto, who commonly refer to abangan as the categorization of Islam in Java. Some claim that abangan refers to the proletarian class and former followers or founders of the Indonesian Communist Party (PKI). Some also said that Islam abangan means adherents of the teachings of Sunan Kalijaga, Syech Siti Jenar, and all the descendants of Sufi masters. In addition, we cannot argue that since the reformation of Indonesia, Islam in Java has changed and has gone forward in a number of ways. As a result, this research paper is trying to explore Islam abangan and its resurgence in detail. I recognize that the resurgence of Islam abangan in Java is somehow intended to address the increasing radicalism and Islamic sectarian. Using an anthropological approach, this research paper attempts to explore what Geertz examined in the "Religion of Java" after a half-century, which needs to be re-examined in the context of contemporary Indonesia.